Toward an optimal degree of openness in IT innovation projects. (26th September 2017) - Bürger, Olga; Moser, Florian
Abstract : In spite of substantial interest in open innovation (OI), both research and practice lack methods that support companies in managing their IT innovation projects (ITIPs) relative to OI. We contribute to the closure of this gap by providing an approach for an ex ante financial evaluation of OI application, which involves developing a theoretical model that determines the optimal degree of openness in ITIPs. Based on our model, we examine relevant causal relationships by analyzing the influence of a company's ability to manage OI and the probability of success in OI application on the theoretical optimum. We find that the optimal openness level is linked with the company's ability to manage OI, which can incorporate organizational, cultural, and technological maturity. To increase the value contribution of OI, companies should focus on a steady improvement in managing OI. The results provide both an indicator for practical decision‐making and a starting point for future research.